A self-paced reading (SPR) study of the effects of processing instruction on the L2 processing of active and passive sentences. (November 2022) - Lee, James F.; Malovrh, Paul A.; Doherty, Stephen; Nichols, Alecia
Recent research on the effects of processing instruction (PI) have incorporated online research methods in order to demonstrate that PI has effects on cognitive processing behaviors as well as on accuracy (e.g. Lee & Doherty, 2019a). The present study uses self-paced reading and a moving windows technique to examine the effects of PI on second language (L2) learners' processing of Spanish active and passive sentences to explore the effects of PI on instructed second language acquisition. One group received PI but the Control group did not. Between group comparisons on passive sentences showed changes in performance for the PI group but not the Control group with the PI group gaining in accuracy and processing speed, specifically faster response times to select the correct picture and faster reading time on passive verb forms. Within group analyses showed changes in the PI group's performance on all dependent variables at the immediate posttest and a subsequent decline in performance at the delayed posttest (8 weeks later). We discuss the implications of our results and treatment format for classroom and hybridized instruction.